Stages of e-democracy: towards an open-source political model. (11th June 2007) - Berthon, P.; Williams, C.B.
Digital networks such as the internet are facilitating and accelerating a change in the relationship between producers and customers. The change embodies a profound shift in power and ideology whereby people become co-producers of value rather than passive consumers. This transition is increasingly mirrored in US politics. Rather than simply choosing between competing candidates, the internet and web-based tools enable voters to become co-producers. In this nascent era of e-Democracy, there is a dearth of conceptual frameworks with which to make sense of the phenomenon. To fill this need, this paper explores how an open-source model of business and politics emerges, its stages and characteristics, and prospects for changing entrenched political processes.